EVALUATION OF STRUCTURAL RESPONSE OF COMPOSITE STEEL-CONCRETE ECCENTRICALLY BUCKLING-RESTRAINED BRACED FRAMES - Bahrami, Alireza; Heidari, Mahmood (Journal of Applied Engineering Science, 2020)
This paper evaluates composite steel-concrete eccentrically Buckling-Restrained Braced Frames (BRBFs) subjected to three different earthquake records. The finite element (FE) software ABAQUS was employed to nonlinearly analyse the BRBs. Comparing the modelling and experimental test results validated the modelling of the BRBF. Three different strong earthquake records of Tabas, Northridge, and Chi-Chi were selected for the nonlinear dynamic analyses. A BRBF was then designed. Thereafter, the designed BRBF was analysed under the earthquake records using the validated modelling method. The lateral displacements and energy dissipations of the frame and shear link rotations were achieved from the analyses of the BRBF and compared. The obtained BRBF results were also compared with its corresponding Eccentrically Braced Frame (EBF) results. It was concluded that in most cases of the lateral displacements and base shears of the frame and also the shear link rotations, the BRBF could perform better than EBF under the earthquake records.